Evaluating the effectiveness of an injury prevention warm-up for female collegiate soccer players - Leigh, S.; Smith, C. N.; Konz, S. (ISBS Proceedings Archive (Michigan), 2023)
Neuromuscular training programs have been shown to decrease injury risk. The purpose of this study was to determine the effectiveness of a soccer-specific injury prevention warm-up program at improving game-time movement patterns. Acceleration and gyroscope data from IMUs and foot forces from smart insoles were collected in-the-field from 16 players during regularly scheduled soccer practice sessions. Change in impact and tibial anterior shear force, and lower extremity kinematics were compared throughout the season with a MANOVA. Tibial anterior shear force and acceleration, knee extension, and knee valgus decreased within each training session (Lambda = 0.387, F18,75 = 12.65, p < 0.01), but not across the season (Lambda = 0.913, F5,18 = 0.34, p = 0.879). This injury prevention warm-up program may be effective at modifying ACL injury risk factors in the short-term but not the long-term.